Marketing support for financial literacy of schoolchildren - Bako, Tamas; Pererva, P. G. (WSEH, 2025)
Marketing support for financial literacy initiatives among schoolchildren is a strategic tool for shaping responsible economic behavior from an early age. By applying social marketing methods, digital communication platforms, and interactive educational campaigns, schools and community organizations can effectively promote financial knowledge and skills. Such support ensures age-appropriate adaptation of materials, fosters motivation through gamification and storytelling, and strengthens cooperation between families, educators, and stakeholders. The integration of marketing approaches into educational practice contributes to the development of practical competencies, long-term awareness, and readiness for participation in the modern economy.
Keywords: marketing; marketing support; financial literacy; schoolchildren; financial environment; financial culture; social marketing; digital communication; gamification; education; economic behavior